Strain‐dependent effectivity, and protective role against enzymes of S‐layers in Lactiplantibacillus plantarum strains - Alp, Duygu (Journal of basic microbiology, 2022)
The present study investigated whether the surface layer (S‐layer), which is known to have a varying effect from strain to strain on aggregation, adhesion ability, also has an effect on the resistance of bacteria to digestive enzymes, phenol, lysozymes. The effect of S‐layers on the resistance against various enzymes, aggregation and adhesion abilities, and strain specificity were determined of eight Lactiplantibacillus plantarum strains. Strains were treated with 5 M lithium chloride (LiCl) to extract the S‐layers, the presence of this layer in those microorganisms was demonstrated by polyacrylamide gel electrophoresis. Scanning electron microscopy was used to visualize the separation of the S‐layer, which surrounds the microorganism, from the microorganism by the LiCl. The images were taken three times, once at the beginning, once 30 min later, and once at the end of this process, which took 2 h in total. The effect against enzymes varied depending on the strain, but it was determined that all the tested strains had a serious loss of viability against phenol in the absence of an S‐layer. Lpb. plantarum DA100 showed a maximum decrease against gastrointestinal system enzymes after the LiCl (96.48 ± 0.03% before and 66.46 ± 0.01% after LiCl). Lpb. plantarum DA255 showed a significant decrease against lysozyme (99.11 ± 0.00% before and 62.80 ± 0.0% after LiCl). Removal of the S‐layer greatly affected the adhesion ability of some strains, while for others there was hardly any change. The results showed that the role of the S‐layer may be strain‐specific, the rate of effect can vary. The primary function of S‐layer proteins is thought to contribute to the adhesion ability of bacteria. There are limited studies that have reported the protective property of this layer against various enzymes, however, our results showed that S‐layer could be one of the resistance strategies developed by bacteria against enzymes.